Single and multirate FFH-OCDMA networks based on PSK modulation formats - Sanches, Anderson Leonardo (2015)
Aiming to achieve the better efficiency in the use of bandwidth (spectral efficiency), as well as a compromise with the energy utilized in the process (power efficiency), the service operators are obliged to change the way in which the information is conveyed. The simplicity of the OOK modulation format has always been the main reason for using it in optical communications. Hence, once the coherent technologies had reached the maturity from a commercial point of view, they have become real alternatives to extend the capacity of networks. In this thesis, the performance of single and multirate FFH-OCDMA networks based on coherent modulation formats is addressed. The following modulation formats are assumed: binary and quadrature phase shift keying (BPSK and QPSK). For single rate networks, BPSK or QPSK are used as the modulation format for all users. For multirate networks, on the other hand, BPSK and QPSK modulation formats are employed for low and high rate transmission users, respectively. For both networks, new bit error rate (BER) formalisms regarding the main deleterious source in OCDMA are derived, namely multipleaccess interference (MAI). The mathematical formalism developed here accounts for any kind of users\' signal waveforms (which are accurately accounted for at the desired user\'s receiver). As a result, it can be successfully used to carry out performance analysis of any OCDMA network. Moreover, it is shown that both low and high rate users can surprisingly achieve similar BER levels. In addition, it is demonstrated that incoherent OOK-based networks are not good candidates for future single and multirate FFH-OCDMA implementations in this interference limited scenario. On the other hand, our results pave the way for BPSK- and QPSK -based networks, which are seen as potential candidates for next generation passive optical networks (NG-PON2), where higher data rates and a vast amount of users will be major network requirements.